Optimizing demand response of a modular water reuse system in a remote Arctic microgrid. (20th April 2022) - Sambor, Daniel J.; Bishop, Samantha C.M.; Dotson, Aaron; Aggarwal, Srijan; Jacobson, Mark Z.
Abstract: Reliance on imported diesel fuel, with high transportation costs, has made power and water treatment expensive in remote diesel microgrids in the Arctic. Past attempts at implementing piped water in these areas have proven difficult due to the high cost of energy to pump, transport, and heat water with imported diesel fuel. A modular Water Reuse (WR) system has been developed to provide more affordable, distributed water service for an individual home lacking running water. However, these WR systems still consume substantial electricity and can burden a household with high energy costs, if powered by the community diesel microgrid. Here we expand a mixed-integer linear optimization model — Food-Energy-Water Microgrid Optimization with Renewable Energy (FEWMORE) — to treat the effects of operating WR systems as dispatchable loads connected to a microgrid. We apply the model to a western Alaska community without piped water to analyze demand response (DR) of WR systems with solar and wind energy. Such an analysis has not yet been articulated by current energy optimization, water treatment, and demand response models for modular water service in microgrids. Integrating a solar photovoltaics (PV) array to power a WR system, as opposed to operating solely off of diesel generation, results in a 3% decrease in total project costs (installing and maintaining solar PV, and electricity purchases from the diesel microgrid) over a 20-year lifetime. Optimally dispatching the water treatment processes results in more savings: a 13% decrease in total project costs and a 37% reduction in diesel use. Highlights: The energy-water nexus can be optimized simultaneously in a remote arctic microgrid. Integrating excess renewable generation reduces costs of water treatment. A water reuse system can be dispatched to operate on intermittent renewables. Optimizing solar capacity decreases diesel fuel costs by 14%. Demand-side management of water treatment reduces diesel costs by 37%.